El mejor remedio para un mal abogado podría ser... ¿otro abogado? - Vargas Guevara, Erick E. (2019)
In this paper, the author states that every lawyer should be compelled to denounce before the corresponding bar association or the judge the cases of abuse of process that damages clients, so the (bad) lawyer, who is behind of these practices, can be punished. The author remarks the fact that, although judges and bar associations are the main protagonists in the punishment of abuse of process, the recognition of this lawyer’s duty can contribute to clients’ rights protection and the consolidation of rule of law. From this perspective, the author proposes that every abuse of process circumstance is perpetrated because a lawyer incited it or because he or she consented it; for this reason, a (bad) lawyer will always be the one who caused the abuse. Precisely, one “remedy” for a lawyer involved in these practices consists in recognize the duty of all lawyers to denounce the (bad) colleagues, in defense of clients and rule of law.